Growth Response of Cacao (Theobroma cacao L.) Clone Iccri 06 H to Various Doses of Humic Acid and NPK Fertilizer - Zulfikri, Robby; Rusmana; Ritawati, Sri; Isminingsih, Sulastri (Jurnal Agroekoteknologi Terapan, 2025)
This study seeks to assess the growth response of cocoa seedlings (Theobroma cacao L.) clone ICCRI 06 H to various concentrations of humic acid and NPK fertilizer. The study was carried out at the Agroecotechnology Laboratory, Faculty of Agriculture, Sultan Ageng Tirtayasa University, and the Integrated Agricultural System (Sitandu) in Banten Province, Curug District, Serang City, Banten. Two components were used in the study: NPK fertilizer (0, 5, 7, 5, and 10 g/plant) and humic acid (0, 10, 20, and 30 g/plant) using a Randomized Block Design (RBD). Observation parameters included plant height, stem diameter, number of leaves, leaf area, leaf chlorophyll index, fresh plant weight, and dry plant weight. The results showed that applying 20 g/plant of humic acid yielded the best results in increasing the number of leaves at 8 Weeks After Plant (WAP) and fresh plant weight at 12 WAP. Humic acid at 30 g/plant showed the highest effect on leaf chlorophyll index at 12 WAP. NPK fertilizer at 5 g/plant was most effective in increasing plant height at 4 WAP, leaf area, and fresh weight of plants at 12 WAP. Meanwhile, the 7.5 g/plant dose yielded the best results for nearly every growth parameter. Only at 4 WAP did a treatment of 10 g/plant result in an increase in plant height. On the dry weight of plants at 12 WAP, there was an interaction between the application of NPK fertilizer at 7.5 g/plant and humic acid treatment at 20 g/plant. Keywords: clone ICCRI 06 H, cocoa, humic acid, NPK fertilizer